The Effects of Waste Autoclaved Aerated Concrete Powders on the Compaction and Consistency Properties of Kaolin - KEVSER, TOLGAHAN; ÇİFTÇİ, HÜSEYİN; GENÇDAL, HAZAL BERRAK; FERCAN, NAZİFE ÖZGE; Arama, Zülal Akbay (Proceedings of the 6th Eurasia Waste Management Symposium, 2022)
The effect of autoclaved aerated concrete (AAC) waste on the compaction and consistency properties of kaolin has been investigated in the scope of this study by an experimental process. The kaolin used in the research is classified in the group of low plasticity silt according to the Unified Soil Classification System (USCS). The AAC planned to be used after mixing with kaolin was supplied as fractured blocks from school construction sites which are specified as waste materials and cannot be used in construction since they got damaged. In this context, consistency and standard compaction tests were applied in the laboratory to investigate the effect of waste aerated concrete additive powder crushed in the laboratory on the geotechnical properties of kaolin-type soils. As a result of the experiments, the AAC additive increased liquid and plastic limits whereas decreased the maximum dry density. In addition, though the soil samples were taken for unconfined compression tests, a layered structure was observed in the samples that prevented carrying out the testing.
Keywords: Compaction; Consistency